(untitled) (Reflection and Critique Law Magazine, 2020)
The Statute of the Person with Disabilities promoted great advances in the legal community by disassociating from the concept of disability to mental or intellectual disability. It reinforced the need to recognize and guarantee the exercise of fundamental rights for people with disabilities, which requires affirmative action by the State and changes in all segments of society. In order to guarantee the dignified existence of persons with disabilities, it established that they are presumably able and changed the theory of disabilities provided for in the Civil Code of 2002.